1977
DOI: 10.1111/j.1476-5381.1977.tb16747.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nicotinic Responses in the Rat Adrenal Medulla and Long‐term Effects of Neonatal Nicotine Administration

Abstract: I The development of nicotinic responses in the rat adrenal medulla was examined at various ages from 1 to 50 days of age by testing the ability of nicotine (10 mg/kg, s.c.) to deplete catecholamines and induce tyrosine hydroxylase. 2 Catecholamines were depleted 25% 3 h after injection of nicotine at all ages tested, but the degree of tyrosine hydroxylase induction 24 h after nicotine increased with age. 3 These data indicate that functional nicotinic receptors are present in the neonatal adrenal medulla befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Hypoxia-evoked catecholamine secretion from AMC involves inhibition of various types of K ϩ channels, leading to depolarization (10,15,17,20,38) Acetylcholine released from the splanchnic nerve activates neuronal nicotinic acetylcholine receptors (nAChRs) on AMC and evokes catecholamine secretion. Although sympathetic innervation to target organs is incomplete in neonates (10, 34), previous studies reported nAChR expression in neonatal AMC (19,32). Given that nicotine is a potent excitatory stimulus to AMC (32), in the present study, we tested the hypothesis that exposing neonatal rats to IH enhances the AMC response to nicotine in a manner similar to that reported for hypoxia.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Hypoxia-evoked catecholamine secretion from AMC involves inhibition of various types of K ϩ channels, leading to depolarization (10,15,17,20,38) Acetylcholine released from the splanchnic nerve activates neuronal nicotinic acetylcholine receptors (nAChRs) on AMC and evokes catecholamine secretion. Although sympathetic innervation to target organs is incomplete in neonates (10, 34), previous studies reported nAChR expression in neonatal AMC (19,32). Given that nicotine is a potent excitatory stimulus to AMC (32), in the present study, we tested the hypothesis that exposing neonatal rats to IH enhances the AMC response to nicotine in a manner similar to that reported for hypoxia.…”
mentioning
confidence: 52%
“…Although sympathetic innervation to target organs is incomplete in neonates (10,34), previous studies reported nAChR expression in neonatal AMC (19,32). Given that nicotine is a potent excitatory stimulus to AMC (32), in the present study, we tested the hypothesis that exposing neonatal rats to IH enhances the AMC response to nicotine in a manner similar to that reported for hypoxia.…”
mentioning
confidence: 61%
“…In the rat, splanchnic control of adrenal catecholamine release is absent during fetal life and at birth. Some studies show that excised neonatal rat adrenals stimulated with depolarizing concentrations of K ϩ evoke a Ca 2ϩ -dependent pronounced release of catecholamines, indicating that neonatal chromaffin cells contain all the machinery necessary for the exocytotic release of chromaffin granule contents (39,43,45,46). Such K ϩ -evoked response requires Ca 2ϩ entry through voltage-dependent Ca 2ϩ channels (VDCCs), as first reported by Douglas and Rubin (12).…”
mentioning
confidence: 99%
“…These results suggest that the adrenal medulla of neonatal rats may be able to secrete partially processed ECP. This type of material was found to be released from chromaffin cells of adult animals, but it occurred only under a specific stimulus [38,43,44] or when high intens ity stimulation with a nonspecific depolarizing agent was applied [39,44,45], These and other biochemical data 793 [32,33,36,45,46] together with the results of histological studies [47] suggest that chromaffin granules in neonatal rats do not present the features observed in mature animals.…”
Section: Discussionmentioning
confidence: 75%
“…However, nicotine treatment in duced depletion of adrenal catecholamines and a persis tent increase of tyrosine hydroxylase activity [32,33], showing that functional cholinergic receptors are present in the gland prior to the establishment of splanchnic in nervation.…”
mentioning
confidence: 99%